2008
DOI: 10.1007/978-3-540-87877-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Value-Driven Coordination Process Design Using Physical Delivery Models

Abstract: Current e-business technology enables the execution of increasingly complex coordination processes that link IT services of different companies. Successful design of cross-organizational coordination processes requires the mutual alignment of the coordination process with a commercial business case. There is however a large conceptual gap between a commercial business case and a coordination process. The business case is stated in terms of commercial transactions, but the coordination process consists of seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…The result is shown in we claim that it is more general than existing approaches and it is easily generalizable beyond e 3 value and BPMN. We have tested our method on earlier cases done by other researchers [18,21] and observed that our application of the method produced similar results to what was obtained in those cases, and we obtained coordination models that are consistent with their corresponding value models according to our denition for consistency. Because…”
Section: Coordination Modelsupporting
confidence: 51%
See 2 more Smart Citations
“…The result is shown in we claim that it is more general than existing approaches and it is easily generalizable beyond e 3 value and BPMN. We have tested our method on earlier cases done by other researchers [18,21] and observed that our application of the method produced similar results to what was obtained in those cases, and we obtained coordination models that are consistent with their corresponding value models according to our denition for consistency. Because…”
Section: Coordination Modelsupporting
confidence: 51%
“…for nding a related coordination perspective and vice versa [8,18,19,20,21], and (2) formal approaches, that dene consistency rules between perspectives that can be checked, e.g. by model checkers [22,23,24].…”
Section: Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they try to produce one from the other (mostly a coordination process model from a business value model) so that in the end both models be consistent with each other [9,10,11]. Pijpers and Gordijn proposed a method that makes an intermediate model (e 3 transition model) based on the business value model by extending it with independent transfers of ownership rights of an object and the actual object itself.…”
Section: Related Workmentioning
confidence: 99%
“…However, there also exists work on ensuring consistency between value and coordination models. For example, Wieringa et al [114] describe a method for constructing physical delivery models that describe the exchanges between partners in the real world. These delivery models close the gap between value and coordination model and show in this way how they are related.…”
Section: Chapter 5 Managing Dependency Relations: Business and Coordmentioning
confidence: 99%